Factors influencing remission in rheumatoid arthritis patients: results from Karnataka rheumatoid arthritis comorbidity (KRAC) study. (25th July 2016) - Chandrashekara, S.; Shobha, Vineeta; Dharmanand, B. G.; Jois, Ramesh; Kumar, Sharath; Mahendranath, Kurugodu M.; Haridas, Vikram; Prasad, Shiva; Singh, Yogesh; Daware, Manisha A.; Swamy, Anupama; Subramanian, R.; et al.
Abstract: Aim: To study the prevalence of remission in rheumatoid arthritis (RA) patients and the influence of different factors like literacy, socioeconomic status, presence of comorbidity and treatment strategy in achieving remission. Methods: The study involved 1990 RA patients who were recruited for the Karnataka Rheumatoid arthritis comorbidity (KRAC) study. Based on the factors evaluated, the study participants were classified as follows: age, < 30 years, 30–39 years, 40–49 years, 50–59 years and ≥ 60 years; educational status, illiterate/no formal education, high school or less, graduate, post‐graduate and doctorate; family income (₹ per annum), < 50 000, 50–100 000, 100–500 000, and > 500 000; duration of illness prior (DOIP): ≤ 6 months, 6–24 months, 24–120 months and > 120 months. Joint counts were performed by a rheumatologist or trained joint assessor. To assess the treatment outcome, the disease activity score was calculated using the Disease activity Score of 28 joints – erythrocyte sedimentation rate (DAS 28–3 ESR). Results: As per the DAS 28–3 ESR score, around 20% ( n = 397) of the study subjects achieved remission. The corresponding mean ± SD of DAS 28–3 ESR noted for remission and non‐remission groups were 2.13 ± 0.42 and 4.32 ± 1.28. The majority of the patients were treated with double disease‐modifying anti‐rheumatic drugs (DMARDs) (60.7%). The likelihood of remission was found to be more in patients who reported DOIP ≤ 6 months. Furthermore, the chances of remission reduced with increase in patient's age and the highest remission rate was noted for 30–39 years age group (59%), followed by 40–49 years (35.4%) and 50–59 years (19.7%). Conclusion: The prevalence of remission noted was around 20%. Early treatment, escalating dose of DMARDs, and patient counseling are important contributing factors for attaining remission.